Competição entre adubos fosfatados em milho (Zea mays L) - Malavolta, E.; Coury, T.; Ranzani, G.; Catani, R. A.; Brasil Sobr., M.O. C.; Arruda, H. V. de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1952)
This paper relates the results of an experiment designed to study the comparative effects of several phosphates applied to corn crops. The following phosphates were applied to a latin square of 6x6: Latif (a rock phosphate), fospal, superphosphate, fertifos, hiperfosfato and serranafosfato (a fusion phosphate). The nutrients were employd at the rates of 200 kg of N (as Chilean nitrate), 200kg of K2O (as muriate of potash) and 200 kg of P205. To correct the acidity and to improve the poor physical conditions of the sandy soil studied limestone (450 kg/Ha) and cotton seed meal (900 kg/Ha) were added to all plots; liming was made one month in advance to the planting. In the second year, in the same place, the split-plot technique was used: half plot received only N and K20 whereas the other half received the same treatment as the year before. The results can be summarized as follows: 1. in the first year, superphosphate of lime, produced better results than the other phosphates; there was no significant difference among fertifos, serranafosfato, and hiperfosfato but these phosphates proved to be superior to fospal and Latif; 2. in the second year, superphosphate, fertifos and serranafosfato produced practically the same effect, being better than hiperfosfato, fospal, and Latif which did not differ signicantly; 3. the increase in yield due to the reapplication of phosphates to the half plots was not advantageous under an economic point of view; however, it is interesting to note that the yield was still benefited in spite of the heavy doses of phosphates applied the year before.